Stargardt Disease: A Rare Case Report: Poster Presentation - Case Report - Resident - Masloman, Anugrah Handini; Kambey, Dave Abraham; Sumual, Gideon; Nursalim, Ade John (Majalah Oftalmologi Indonesia, 2023)
Introduction : To report a stargardt disease case Case Illustration : A 14 year young boy presented with chief complaints of blurry vision in both eyes since childhood. Progressive loss in his ability to differentiate between faces, colors and point out details of objects. On ocular examination, his visual acuity was 1/60 with retinoscopy value revealed +2.00 Dsph and was unable to read plates of Ishihara chart in both eyes. On indirect ophthalmoscopy optic disc were normal with sharp margins and orange color and absent foveal reflex in both eyes. Numerous small whitish flecks were seen around the macula in both the eyes with an ill-defined circular lesion was seen at the macula with beaten bronze appearance. Supportive therapy such as correction with low vision aids or the provision of sun protective glasses can help in the daily lives of patients. Discussion : Stargardt disease is an inherited macular degeneration that typically presents in the first two decades of life. The prevalence is in the region of 1 in 8–10,000 individuals. Study reported an annual incidence of 0.127 per 100,000. This case was also rarely reported in Indonesia. The age of onset and rate of progression vary greatly, with most experiencing symptoms in their teens or earlier. Conclusion : Stargardt disease case has been reported in a 14 year young boy. Progressive vision loss can be the only vision complaint from the patient. Supportive therapy such as correction with low vision aids or the provision of sun protective glasses can help in the daily lives of patients.